Ancient Palestine and the creation of an Israelite state - Yaacob, Solehah@Nik Najah Fadilah (IIUM Press, 2011)
The most enduring cultural myth of the Jewish people is the idea of the ‘Promised Land’. The propagation of ‘Palestine’ as the ‘true Jewish homeland’ continues to this day among the circles of biblical studies and thus denies ancient Palestine its own history. According to Keith W. Whitelam, “It`s concern with the broad themes of history, settlement, demography and economy was conceived to be an antidote to the standard histories of ancient Israel based upon the biblical traditions which have dominated biblical studies since the nineteenth century. Biblical studies never gave chance to ancient Palestinians (= Arabs) as the original settlers of the land”.